Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-52557-z
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of femXAB genes and fnbp mediated biofilm pathways in OS-MRSA clinical isolates

Abstract: Methicillin-Resistant Staphylococcus aureus (MRSA) is a significant threat to human health. Additionally, biofilm forming bacteria becomes more tolerant to antibiotics and act as bacterial reservoir leading to chronic infection. In this study, we characterised the antibiotic susceptibility, biofilm production and sequence types (ST) of 74 randomly selected clinical isolates of S. aureus causing ocular infections. Antibiotic susceptibility revealed 74% of the isolates as resistant against one or two antibiotics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…aureus biofilm encoded by the ica operon and expression of the ica operon is under the control of SarA. Apart from PIA, SarA also controls adhesion proteins FnbA and FnbB. As a downstream effect of SarA downregulation, expressions of icaA , icaD , fnbA , and fnbA were also decreased by carvacrol treatment. On the other hand, interaction of carvacrol with CrtM, the first enzyme of the staphyloxanthin biosynthetic pathway, was investigated using molecular docking analysis as prior studies reported CrtM as an efficient drug target to inhibit staphyloxanthin synthesis. ,, Results revealed the strong binding of carvacrol with CrtM through hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…aureus biofilm encoded by the ica operon and expression of the ica operon is under the control of SarA. Apart from PIA, SarA also controls adhesion proteins FnbA and FnbB. As a downstream effect of SarA downregulation, expressions of icaA , icaD , fnbA , and fnbA were also decreased by carvacrol treatment. On the other hand, interaction of carvacrol with CrtM, the first enzyme of the staphyloxanthin biosynthetic pathway, was investigated using molecular docking analysis as prior studies reported CrtM as an efficient drug target to inhibit staphyloxanthin synthesis. ,, Results revealed the strong binding of carvacrol with CrtM through hydrogen bonding.…”
Section: Discussionmentioning
confidence: 99%
“…If an OS-MRSA is wrongly identified as MSSA and beta-lactam antibiotics are given, the oxacillin resistance subpopulation will be selected and will be responsible for treatment failure [ 90 ]. In another study, 11 OS-MRSA isolates were isolated from ocular infections [ 91 ]. Boonsiri et al analyzed 43 OS-MRSA clinical isolates and found that cefoxitin performed better (19/43 isolates correctly identified as MRSA) than the automated system or the Etest in managing OS-MRSA, but was still not optimal, so a confirmatory PCR might be required [ 92 ].…”
Section: Molecular Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%
“…Experiments were performed in triplicate and results were presented as 10.3389/fmicb.2022.980191 Frontiers in Microbiology 04 frontiersin.org mean ± SD. The data were analyzed as described before (Brahma et al, 2019).…”
Section: String Test and Biofilm Formation Assaymentioning
confidence: 99%